2017
DOI: 10.1128/genomea.01009-17
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Klebsiella pneumoniae Phages SopranoGao, MezzoGao, and AltoGao

Abstract: The Klebsiella pneumoniae phages SopranoGao, MezzoGao, and AltoGao were isolated from the Seneca Wastewater Treatment Plant in Germantown, MD. The following reports the complete genome sequence of these bacteriophages and describes their major features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The φBO1E phage belongs to the Podoviridae family and is a member of the recently described Drulisvirus genus [ 27 ]. Even if the information on the infection specificity of Drulisvirus phages is currently available in a limited number of cases, i.e., KpV41, KpV48, KpV71, KpV74, KpV475 [ 28 ], myPSH1235 [ 29 ], πVLC1-4 [ 30 ] and vB_KpnP_IME337 [ 31 ], for most of these phages a perfect correlation between the bacterial cps type and phage susceptibility has been demonstrated [ 10 , 28 , 30 , 31 ] while this information is lacking or a broader specificity has been determined in a limited number of studies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ] ( Table S2 ). This is in line with our results and, together with the observation that these phages possess a pectate lyase domain in their terminal fibers, suggests that this genus is characterized by the ability of targeting bacterial polysaccharides for the early infection steps.…”
Section: Discussionmentioning
confidence: 99%
“…The φBO1E phage belongs to the Podoviridae family and is a member of the recently described Drulisvirus genus [ 27 ]. Even if the information on the infection specificity of Drulisvirus phages is currently available in a limited number of cases, i.e., KpV41, KpV48, KpV71, KpV74, KpV475 [ 28 ], myPSH1235 [ 29 ], πVLC1-4 [ 30 ] and vB_KpnP_IME337 [ 31 ], for most of these phages a perfect correlation between the bacterial cps type and phage susceptibility has been demonstrated [ 10 , 28 , 30 , 31 ] while this information is lacking or a broader specificity has been determined in a limited number of studies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ] ( Table S2 ). This is in line with our results and, together with the observation that these phages possess a pectate lyase domain in their terminal fibers, suggests that this genus is characterized by the ability of targeting bacterial polysaccharides for the early infection steps.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the problem of the development and spread of antibiotic resistant bacteria, phages have been investigated as alternative antimicrobial agents to treat bacterial infections in humans 12 14 , and several studies have isolated and characterize phages specific for K. pneumoniae 15 18 . For example K. pneumoniae phage KN2 19 , NTUH-K2044-K1-1 20 , phage KP36 21 have exhibited robust activities with high target specificity, possibly as a consequence of their depolymerases and polysaccharide degrading enzymes which can degrade polysaccharides such as capsular polysaccharide (CPS), extracellular polymeric substance (EPS) and biofilm 22 .…”
Section: Introductionmentioning
confidence: 99%
“…By using progressiveMauve 2.4.0, we found that Skenny shares high nucleotide identity with various T1-like phages, including 96% and 98% identity with K. pneumoniae phages KPN N141 (GenBank accession number MF415412) and MezzoGao (GenBank accession number MF612072), respectively (21). There are 78 genes predicted to encode proteins for Skenny, but no tRNAs were detected.…”
Section: Announcementmentioning
confidence: 99%